Suicide Problem. A Descriptive Study of Hospital Admissions in the General Hospital of Paraná City Between 2018 and 2022 (Revista de Psicología, 2024)
Suicide is a public health problem. The present study was carried out in the context of on-call admissions at the Paraná, Entre Ríos, Argentina, San Martín Hospital that had any of the following reasons for consultation: suicide attempt, self-injurious behaviors without intent to kill, and suicide attempts in context of problematic substance use in the period 2018-2022. The objectives were: to describe the frequency of reasons for consultation within suicidal problems in the period 2018-2022; to evaluate the association between the reasons for consultation and the year of admission; the reasons for consultation and sex; the reasons for consultation and the age of the subjects; and describe the protective and risk factors. We worked with 893 clinical histories, which corresponded to 295 men (33%) and 598 women (67%) between 15 and 93 years of age (M= 31.16 DS= 14.76). A questionnaire prepared by experts in the field of mental health at the hospital was used. Frequencies were obtained and Pearson's Chi squares were calculated to assess the association between categorical variables. An association was found between the reason for consultation and the year of admission, with an increase in the frequency of self-harm without the intention of killing in 2022 and an increase in suicides in the context of problematic consumption in 2021. An association was observed between the reason for consultation and age with an increase in suicide attempts in young people and an increase in self-harm without the intention of killing in middle adulthood. An association was observed between the reason for consultation and age. As a risk factor, the presence of stressful life factors stands out and family support stands out as protective factors, although schooling and peer support decrease in adolescents and young people.
Keywords: suicide; self-harm; hospital